Negative lattice expansion-induced upconversion luminescence thermal enhancement in novel Na2MoO4:Yb3+, Er3+ transparent glass ceramics for temperature sensing applications. Issue 4 (11th January 2023) - Zi, Yingzhu; Cun, Yangke; Bai, Xue; Xu, Zan; Haider, Asif Ali; Qiu, Jianbei; Song, Zhiguo; Huang, Anjun; Zhu, Jialun; Yang, Zhengwen
Abstract : Negative lattice expansion-induced upconversion luminescence (UCL) thermal enhancement can efficiently solve thermal quenching of lanthanide ions, and the temperature sensing characteristics can be obtained by combining with fluorescence intensity ratio technology. Abstract : Negative lattice expansion-induced upconversion luminescence (UCL) thermal enhancement can be used to efficiently solve the problems of thermal quenching of lanthanide ions, and it can be combined with traditional fluorescence intensity ratio technology to obtain temperature-sensing characteristics. In this work, linear negative thermal expansion of the lattice of Na2 MoO4 :Yb 3+, Er 3+ transparent glass ceramics was examined after fabrication by a low-temperature co-sintering approach. Thermal enhancement of UCL at 525 and 806/860 nm for the glass ceramics was caused by an increase in energy transfer between Yb 3+ and Er 3+ ions induced by the linear negative thermal expansion properties of orthorhombic Na2 MoO4 nanoparticles. Combining the UCL characteristics of a positive thermal expansion tellurite glass matrix and negative thermal expansion Na2 MoO4 :Yb 3+, Er 3+ nanoparticles, a novel glass ceramic temperature sensor was obtained. The temperature relative sensitivity was manipulated by selecting different UCL spectral modes up to 3.14% K −1 (313 K), which provided a more optimal performance than many glass ceramics previously reported. The cycle measurement of the UCL response alternating between 313 and 573 K indicates excellent repeatability, and thus, there is the potential for successful application of Na2 MoO4 :Yb 3+, Er 3+ transparent glass ceramics as a new generation of temperature sensors.